Study of the Frost Resistance of HDFC Based on a Response Surface Model and GM (1,1) Model - Zeli Liu; Jiuhong Jiang; Ziling Xu (Advances in Materials Science and Engineering, 2022)
Taking high ductility concrete (HDFC) as a research object, the frost resistance of HDFC in freeze-thaw cycle tests is studied, accurately predicted, and quantitatively described. Taking the relative dynamic elastic modulus as the evaluation index, the response surface model and GM (1,1) model were used to study the frost resistance of HDFC, and the advantages and disadvantages were evaluated. Design-Expert software was used to establish a response surface model to study the effects of polyvinyl alcohol fiber (PVA) length, polyvinyl alcohol fiber volume content, and number of freeze-thaw cycles on the frost resistance of HDFC, and a fitting relationship model between the relative dynamic elastic modulus and these three factors was established. The results show that the influence of PVA fiber content on the frost resistance durability of HDFC is higher than that of the PVA fiber length, but the effect of the external environment on the degree of deterioration for HDFC is greater than the improvement of the properties of the material itself; that is, the freeze-thaw cycling has a greater effect than the PVA fiber content and length. Grey system theory was introduced in the HDFC freezing resistance test, and the change rule for the relative elastic modulus and the average relative error for the GM (1,1) model for varying PVA fiber length and content was determined to be less than 5%. It is concluded that the freezing resistance prediction accuracy for HDFC based on the GM (1,1) model is higher than that of the response surface model. The GM (1,1) model can be used to accurately predict the degree of damage caused by freezing and melting cycles for HDFC.